ANALISIS ORGANOLEPTIK EDIBLE STRAW DARI BUAH NANAS (ANANAS COMOSUS L.) SUBGRADE VARIETAS QUEEN - Devi Urianty Miftahul Rohmah; Wendianing Putri Luketsi; Sri Windarwati (Agroindustrial Technology, University of Trunojoyo Madura, 2020)
This study aimed to determine the formulation of carrageenan and sorbitol concentration to the organoleptic value of edible straw from subgrade pineapple Queen variety which was most preferred by panellists. This study uses a Completely Randomized Design (CRD) method of 2 factors. The first factor is carrageenan (K) concentration which consists of 2 levels, namely 2% (b / b) and 4% (b / b) to 400 grams of pineapple puree. The second factor is sorbitol (S) concentration which consists of 2 levels namely 8% (v / b) and 10% (v / b) to 400 grams of pineapple puree. Organoleptic analysis carried out using a hedonic test which included colour, aroma, taste, texture, ease of sucking, and overall.